2013
DOI: 10.1103/physrevstab.16.044201
|View full text |Cite
|
Sign up to set email alerts
|

Single-knob beam line for transverse emittance partitioning

Abstract: Flat beams feature unequal emittances in the horizontal and vertical phase space. Such beams were created successfully in electron machines by applying effective stand-alone solenoid fringe fields in the electron gun. Extension of this method to ion beams was proposed conceptually. The present paper is on the decoupling capabilities of an ion beam emittance transfer line. The proposed beam line provides a single-knob tool to partition the horizontal and vertical rms emittances, while keeping the product of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 17 publications
7
33
0
Order By: Relevance
“…The theoretical framework and analytical tools developed in the present study are also expected to be effective for the current theoretical and experimental investigations of emittance exchange technologies. [44][45][46][47][48][49][50] …”
Section: Discussionmentioning
confidence: 99%
“…The theoretical framework and analytical tools developed in the present study are also expected to be effective for the current theoretical and experimental investigations of emittance exchange technologies. [44][45][46][47][48][49][50] …”
Section: Discussionmentioning
confidence: 99%
“…It can be shown that the two eigenemittances are given by (EMTEX) [11,12]. For the RTFB transformation experiment, κ 0 is given by κ 0 = Bs 2(Bρ)c , where B s and (Bρ) c are the solenoidal magnetic field and beam rigidity at the cathode, respectively.…”
mentioning
confidence: 99%
“…[11]. The focusing coefficients of the skew-quadrupoles are kept fixed at the values used to decouple the beam produced by a solenoidal field of 1.0 T, with the conditions of zero space-charge and zero acceleration.…”
mentioning
confidence: 99%
See 2 more Smart Citations